Transobturator tape in the treatment of women with urinary incontinence - Ruth Alexandra Ramos Villacís; Alfredo Daniel Pucha Landacay; Adriesther González Lorié (Centro Provincial de Información de Ciencias Médicas, 2023)
Treatment in women with urinary incontinence is different from that in men. In this regard, the techniques of tension-free vaginal tape and transobturator tape are currently used to lift the bladder or urethra, or both, back to the normal position. The surgical procedure with a monofilament braided polypropylene transobturator band is among the major outpatient surgeries and is shown to be an effective and safe treatment, with minimal risks. In this paper, some aspects of incontinence in women, its diagnosis, prevention and associated risk factors are briefly reported, as well as the entire process of applying this technique.